Thermococcus kodakarensis modulates its polar membrane lipids and elemental composition according to growth stage and phosphate availability - Meador, Travis B.; Gagen, Emma J.; Loscar, Michael E.; Goldhammer, Tobias; Yoshinaga, Marcos Y.; Wendt, Jenny; Thomm, Michael; Hinrichs, Kai-Uwe (Frontiers in Microbiology, 2014)
We observed significant changes in the elemental and intact polar lipid (IPL) composition of the archaeon Thermococcus kodakarensis (KOD1) in response to growth stage and phosphorus supply. Reducing the amount of organic supplements and phosphate in growth media resulted in significant decreases in cell size and cellular quotas of carbon (C), nitrogen (N), and phosphorus (P), which coincided with significant increases in cellular IPL quota and IPLs comprising multiple P atoms and hexose moieties. Relatively more cellular P was stored as IPLs in P-limited cells (2-8%) compared to control cells (< 0.8%). We also identified a specific IPL biomarker containing a phosphatidyl-N-acetylhexoseamine headgroup that was relatively enriched during rapid cell division. These observations serve as empirical evidence of IPL adaptations in Archaea that will help to interpret the distribution of these biomarkers in natural systems. The reported cell quotas of C, N, and P represent the first such data for a specific archaeon and suggest that thermophiles are C-rich compared to the cell carbon-to-volume relationship reported for planktonic bacteria.